From toots to returns: a thesis on financing climate adaptation via nature-based solutions in South Africa - Davis, Grant (Graduate School of Business (GSB), 2025)
The profound repercussions of climate change manifest acutely within Africa. As the region grapples with the disruptive forces of erratic weather patterns which have resulted in widespread droughts and floods impacting the most vulnerable of its people. The exigency to adapt emerges as a pressing mandate, underscoring the critical imperative for timely and effective climate resilience strategies. Given the inadequate public and international financing for adaptation, there is therefore an urgent need to tap into alternative sources, particularly those from the private sector. Nature-based solutions (NbSs) encompass actions and strategies that rely on the use of natural processes to address environmental challenges and have been highlighted as a potentially cost effective and eco-system enhancing means of building climate resilience. This exploratory study investigated the financing landscape in South Africa to determine barriers and success factors that hinder or enable private sector investment in NbS for climate adaptation. This study was conducted using primary data in the form of 26 interviews with professionals from across the financing landscape. Through the application of grounded theory, this study considered how industry professionals understand NBS and their perceptions of the financing of adaptation. This study identified factors which hinder the effective participation of the private sector in investing in NBS for climate adaptation. These can be categorised as: market related, project level, policy and institutional, skills and capacity, and information or data gaps. Furthermore, the study found that, whilst Development Finance Institutions have made advances in supporting climate adaptation NBSs, there isstill insufficient progressin this area. It is also evident that leveraging private sector investment effectively will require an innovative approach that recognises the existing challenges associated with climate adaptation. Whilst many difficulties lie ahead, what is clear from the study is that the sector is working towards overcoming these challenges. This study provides a significant contribution towards understanding the South African context for all stakeholders operating in this space.